Selected applications of cash flow models of life insurance. - Hoang, Thu Giang; Janeček, Martin; Fojtík, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
The thesis deals with the practical applications of a cash flows model in a life insurance company accompanied by illustrative numerical examples. Specifically, the applications presented are profit testing, calculation of value of liabilities, liability adequacy test and estimation of company value (embedded value). The thesis is structured in three chapters. Firstly, life insurance companies and their products are introduced. Then the cash flows model and its components are described in detail. The third chapter presents each application one by one, firstly of their main principle and then demonstrates with a real example of endowment product. The thesis is a consolidated source of cash flows model’s application in life insurance.
Vedoucí práce: Martin Janeček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses